Peran Suami dalam Perlindungan Perempuan terhadap Kekerasan dalam Rumah Tangga Perspektif Hukum Agama Hindu - Ni Wayan Eka Sumartini (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Marriage is one way to achieve happiness in the family. According to Hinduism, marriage is a way to carry out obligations as children, obligations as husband and wife, and obligations as parents. However, in practice, marriages do not always run peacefully and beautifully. Sometimes there are disputes in the household that lead to violence. Domestic violence that makes women the victims often occurs. This research aims to emphasize the role of husbands in the household to protect women from domestic violence. This research uses literature study with descriptive data analysis. The research results show that in Hindu religious teachings, husbands have a very large role in protecting their family. The husband's position in the patrilineal system adopted by Balinese Hindus not only gives the husband a high position and is the most respected in the family, but behind this a husband has a big responsibility to maintain the integrity of his household. The husband has a duty to protect his family and provide peace to achieve a happy and eternal married life in accordance with the purpose of marriage.